N-doped magnetic covalent organic frameworks for preconcentration of allergenic disperse dyes in textiles of fall protection equipment. Issue 27 (27th June 2019) - Wu, Fang-Fang; Chen, Qing-Yin; Ma, Xiu-Juan; Li, Ting-Ting; Wang, Li-Feng; Hong, Jing; Sheng, Ye-Hong; Ye, Ming-Li; Zhu, Yan
Abstract : A novel N-doped magnetic covalent organic framework (N-Mag-COF) has been synthesized. Abstract : A novel N-doped magnetic covalent organic framework (N-Mag-COF) has been synthesized. It has been evaluated in the magnetic dispersive solid phase extraction (Mag-dSPE) procedure for textiles of fall protection equipment prior to the analysis of allergenic disperse dyes by liquid chromatography-tandem quadrupole mass spectrometry (LC-MS/MS). Compared with the matrix dilution procedure, much higher sensitivity of the analytical method has been achieved by the N-Mag-COF Mag-dSPE procedure. Furthermore, under the optimum conditions, the level of matrix effects can be dramatically reduced by the N-Mag-COF Mag-dSPE procedure with satisfactory recoveries in the range of 72.2–107%. The precision of the developed method was satisfactory, with relative standard deviations (RSDs) ranging from 2.3% to 7.1%. The limits of detection (LODs) and limits of quantification (LOQs) of 19 allergenic disperse dyes were in the range of 0.021–0.58 μg kg −1 and 0.069–1.91 μg kg −1, respectively. The developed analytical method was successfully applied to the analysis of 20 textile samples of fall protection equipment, in which disperse yellow 39 was found in two samples with concentrations at 0.081 μg kg −1 and 0.062 μg kg −1, respectively. The developed method can be applied to routine analyses for the determination of 19 allergenic disperse dyes in textiles of fall protection equipment.